(untitled) (Fiep Bulletin - online, 2015)
Brazil is a country constituted by an enormous cultural diversity, and involves inside this context different people, religions and dialects. Relegated to a historical past of fights and resistances, the Brazilian natives, in spite of the constant dizimation menace, still survive in the poverty of the Brazilian society. So, an option was made, in this study, to think over the indigenous culture, especially the Avá-Guarani of Ocoy tribe, in the municipal district of São Miguel do Iguaçu-PR with the objective to improve the glance that is thrown about their lives. However, it was tried to rescue the games, plays and indigenous toys, starting from the remembering and memories of an Indian, verifying at the present time, if these that they were referred by him, still continue among the children of the tribe. The present research is characterized as being qualitative, used the ethnic description and the pragmatic study of the language, having as sampling a tribe member, the Headman. He was selected by presenting several characteristics that facilitated the development of the researches, among them, the domain of the Portuguese language. Through a reading of the toys, plays and games for him characterized, it could be made a new reading of his habits for a better understanding of these, taking in consideration his life way in time and space. It was verified in this research, that the great majority of the games, plays and toys rescued in the memory and the social actor’s memories, are not present anymore among the tribe children, but just in the older natives’ memories. For the little indians they remain the games of the non Indians